An analysis of ESL students’ multimedia project work: a case of language transfer - Wan Mansor, Wan Fara Adlina; Muhari, Noraisah (2010)
This study seeks to investigate the case of language transfer by using an analysis of errors adopted from Elliott (1983) towards ESL students’ Multimedia Project Work saved in CDs. The data for the study were obtained from six sets of CDs produced by the group of previous ESL students from Faculty of Computer Science, Universiti Teknologi Malaysia Skudai for their English for Academic Communication course (UHB 1412). The CDs were analyzed via checklist in order to identify the types of errors and patterns of the errors made. The analysis of the students’ Project Work has shown that there are twelve types of errors that are closely related to the case of language transfer. Verbs contributed the highest percentage of errors in this study while the infinitive-to is the lowest. Errors are unavoidable in learning a second language. Subjects tend to make errors in this area as indication of their confusion of both languages. Therefore, they tend to use their knowledge of first language to cope with the insufficient knowledge of a second language. Moreover, the analysis also indicates that the subjects faced two categories of errors that are known as Intra-lingual errors and Inter-lingual errors due to conscious and subconscious transfer. Analyzing these errors would give insights into the reasons for the language transfer or interference underlying the occurrence of these errors as pedagogical implication that could help students to improve their knowledge on both Languages (L1 and L2).